Ciclo reprodutivo de Philodryas patagoniensis (Serpentes: Dipsadidae) no Sul do Brasil - Loebens, Luiza (2015)
Tropical snakes present a greater diversity of reproductive patterns influenced by intrinsic factors and environmental conditions. Reproductive cycles may be more plastic in tropical areas due to the climatic complexity. However, studies of snake reproductive biology are more developed with species by temperate region. So, we investigated the reproductive biology of the snake Patagonia Green Racer (Philodryas patagoniensis) through anatomical and histological analysis of specimens from south Brazil. For that, individuals deposited in zoological collections were used to analyze the males testes, ductus deferens, and kidney, and the females ovarium and oviducts. The spermatogenic peak coincides with the mating season, although sperm was seen stored in ductus deferens all over the year. The females stay reproductively active during an extended period showing vitellogenic follicles in all the seasons, beside that the vitellogenic peak occurs during winter-spring. Females have ability to produce multiple clutches in the same reproductive season with sperm long-term stored. Sexual body size dimorphism was evident being females significantly larger and heavier than males, beside that males have larger tails than females. Males the sexual maturity in smaller sizes than females. Fecundity in P. patagoniensis is correlated with maternal body size, with larger females producing follicles and eggs in greater amount and size. The number of eggs produced by each female varies between five and 22. The seasonal activity is determined by the reproductive cycle, since males and females shows activity peak (spring) coinciding with the mating season, and juveniles were more abundant in the time of recruitment (summer). The seasonal changes in temperature must be the main factor influencing the snakes reproductive activity in subtropical climate. Altogether, our results indicate that P. patagoniensis has a seasonal pattern of reproduction in south Brazil.